Hubungan Olahraga Bulutangkis Dengan Kapasitas Vital Paru Pada Pemain Bulutangkis - Faj'ri Romadhona, Nurul, Isnaini Herawati, S.Fis.,Ftr.,M.Sc, Dwi Kurniawati SSt.FT, M.Kes (2015)
Background: Vital lung capacity associated with a person's ability to work the muscles. Someone does work, the more severe the work done, the higher oxygen consumption. Badminton affect lung function in the player which resulted in an increase in lung vital capacity and develop greater endurance in the muscles of respiration. By having good cardiovascular endurance, then a player can play badminton longer so it is not susceptible to fatigue. The Objective of Research: This study aims to determine the relationship of badminton with lung vital capacity in badminton players. The Benefit of Research: In this research are expected to provide new insight into the sport of badminton in improving lung vital capacity in badminton players . The Method of Research: The research design was observational analytic with cross sectional design. Total sample is 60 badminton players. Data collection research using questionnaires and spirometry measurements. Data were analyzed using Chi Square test. Result of the Research: Chi Square test results have 0,001 p value <0.05 was concluded that there is a relationship between the sport of badminton with lung vital capacity. Value odds ratio was 12.325 with a 95% confidence level and CI between 3.342 to 45.449, so that the subjects with the sport of badminton is done routinely have vital capacity ratio of normal lungs 12 times higher than those who did not regularly. Conclusion: Based on the results of the data analysis is concluded there is a relationship between the sport of badminton with lung vital capacity.